Perceptions of Students in Relevance of Management Course in Engineering Disciplines: A Higher Education-Implications for a 21st-Century Curriculum - Lastimado Jr, Alberto E. (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study addresses the critical need to understand how engineering students perceive the relevance of engineering management education in preparing them for these multifaceted roles. Specifically, this research evaluates the perspectives of undergraduate engineering students in the Philippines regarding the significance of engineering management in their respective disciplines, its role in skill development, and the challenges encountered. A mixed-methods approach was employed, gathering data from 396 undergraduate engineering students through surveys, brief written responses, and interviews. Findings indicate that a significant majority of students hold favorable impressions, with 86.8% believing the knowledge gained will be valuable and 84.5% affirming that the course develops essential analytical and critical thinking skills. Students generally recognize the importance of engineering management in fostering fundamental abilities crucial for their future careers. However, a notable challenge is the perceived workload, with 52.7% of students finding management-related coursework demanding. The research illustrates the importance of integrating well-designed engineering management education within engineering curricula. The findings highlight the importance of equipping future engineers with the managerial expertise and soft skills the complexities of the 21st-century workforce and inform strategies for curriculum enhancement.